Historical Trajectories of Indonesia’s Fiscal Gap and Military Spending, 2003–2023 - Aris Marsudiyanto; Athor Subroto; Bambang Permadi Soemantri Brodjonegoro; A. Hanief Saha Ghafur (Paramita: Historical Studies Journal, 2025)
Abstract: Military spending reflects a nation's priorities and its geopolitical orientation, but in Indonesia it has been compromised by chronic fiscal deficits. The aim of this research was to analyze the historical trajectories of Indonesia’s fiscal gap in military spending from 20023 to 2023 by situating national development within broader global conflicts, including Russia-Ukraine war. A historical method was employed by applying synchronic and diachronic analysis, drawing on archival data from the state budget, official reports from the Ministry of Finance, publications from the SIPRI, and policy documents. The findings demonstrated that historical patterns of defence expenditure consistently revealed a widening fiscal gap between projected requirements and available fiscal capacity. Global geopolitical tensions intensified military modernisation and imposed additional burdens on national budgets. The study concludes that Indonesia’s defence financing challenges cannot be examined solely through contemporary fiscal debates but must be interpreted within a long-term historical narrative of deficit budgeting and external shocks. The contribution of this research lies in advancing historical scholarship on fiscal policy and defence spending while providing policymakers with insights into alternative financing strategies grounded in past experiences and institutional legacies. Abstrak: Belanja militer mencerminkan prioritas suatu negara sekaligus orientasi geopolitiknya, namun di Indonesia hal ini terhambat oleh defisit fiskal yang bersifat kronis. Penelitian ini bertujuan menganalisis trajektori historis kesenjangan fiskal dalam pembiayaan pertahanan Indonesia selama periode 2003–2023 dengan menempatkan dinamika nasional dalam konteks konflik global, termasuk perang Rusia–Ukraina. Metode sejarah digunakan dengan menerapkan analisis sinkronik dan diakronik, berdasarkan data arsip Anggaran Pendapatan dan Belanja Negara, laporan resmi Kementerian Keuangan, publikasi SIPRI, serta dokumen kebijakan. Temuan penelitian menunjukkan bahwa pola historis pengeluaran pertahanan secara konsisten mengungkapkan pelebaran kesenjangan fiskal antara kebutuhan yang diproyeksikan dan kapasitas fiskal yang tersedia. Ketegangan geopolitik global semakin mendorong modernisasi militer dan menambah beban pada anggaran nasional. Penelitian ini menyimpulkan bahwa tantangan pembiayaan pertahanan Indonesia tidak dapat dipahami hanya melalui perdebatan fiskal kontemporer, melainkan harus ditafsirkan dalam narasi historis jangka panjang mengenai defisit anggaran dan guncangan eksternal. Kontribusi riset ini terletak pada pengembangan kajian sejarah kebijakan fiskal dan belanja militer, sekaligus memberikan wawasan bagi pembuat kebijakan terkait strategi pembiayaan alternatif yang berpijak pada pengalaman historis dan warisan institusional.